Process and difference : between cosmological and poststructuralist postmodernisms - Keller, Catherine, 1953-; Daniell, Anne, 1965- (SUNY series in constructive postmodern thought., 2002)
"The similarities and creative tensions between French-based poststructuralism and Whiteheadian process thought are examined here by leading scholars. Although both approaches are labeled "postmodern," their own proponents often take them to be so dissimilar as to be opposed. Contributors to this book, however, argue that processing these differences of theory at a deeper level may cultivate fertile and innovative modes of reflection. Through their comparisons, contrasts, and hybridizations of process and poststructuralist theories, the contributors variously redefine concepts of divinity and cosmos, advance the interaction between science and religion, and engage the sex/gender and religious ethics of otherness and subjectivity."--Jacket